Performance of Covid-19 antigen rapid diagnostic tests for self-testing compared with antigen testing by professionals and molecular tests: a systematic review and meta-analysis [research data] - Katzenschlager, Stephan; Brümmer, Lukas E.; Schmitz, Stephani; Tolle, Hannah; Manten, Katharina; Gaeddert, Mary; Erdmann, Christian; Lindner, Andreas; Tobian, Frank; Grilli, Maurizio; Pollock, Nira R.; Mace, Aurélien; et al. (Universität, 2022)
Background: Self-testing has been identified as an effective tool to bridge the testing gap for a number of infectious diseases; however, the perf...
Gesehen am 02.12.2022
Keywords: Forschungsdaten; Datenbank